2021
DOI: 10.3390/jcm10092016
|View full text |Cite
|
Sign up to set email alerts
|

Radiological Cardiothoracic Ratio in Evidence-Based Medicine

Abstract: The cardiothoracic ratio (CTR), expressing the relationship between the size of the heart and the transverse dimension of the chest measured on a chest PA radiograph, is a commonly used parameter in the assessment of cardiomegaly with a cut-off value of 0.5. A value of >0.5 should be interpreted as enlargement of the heart. The following review describes the current state of available knowledge in terms of contentious issues, limitations and useful aspects regarding the CTR. The review was carried out on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 28 publications
2
32
0
Order By: Relevance
“…While the MHCD has little change from 10.47 cm to 10.16 cm, the MHTD has relatively large change, from 24.71 cm to 25.40 cm. As a consequence, the cardiothoracic ratio becomes 0.4002, which is below the normal range of 0.42 -0.50 [43]. The result of learning perspective deformation from 0 • single view is displayed in Fig.…”
Section: Results On Chest Datamentioning
confidence: 92%
See 1 more Smart Citation
“…While the MHCD has little change from 10.47 cm to 10.16 cm, the MHTD has relatively large change, from 24.71 cm to 25.40 cm. As a consequence, the cardiothoracic ratio becomes 0.4002, which is below the normal range of 0.42 -0.50 [43]. The result of learning perspective deformation from 0 • single view is displayed in Fig.…”
Section: Results On Chest Datamentioning
confidence: 92%
“…The results of one patient in chest X-ray imaging are displayed in Fig. 11, where the cardiothoracic ratio is assessed as an exemplary clinical application [43]. In the reference image (Fig.…”
Section: Results On Chest Datamentioning
confidence: 99%
“…However, it is important to remember that these patients with a positive ECG-LVH criterion and/or chest radiograph suggestive of cardiac enlargement should not be excluded from further diagnostic processes. Despite the strongest agreement with CMR-LVH for a CAR 2 E 2 score of ≥3, when compared to chest radiograph parameters indicating cardiac enlargement or ECG-LVH criteria, studies have shown that ECG and chest radiograph used alone are also useful in screening for LVH [16,36].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, CTR and TCD may be influenced by several other factors, such as pericardial fat, elevation of the diaphragm either due to poor inspiration or obesity, the breathing phase or thoracic alterations (e.g., severe scoliosis, pectus excavatum) [2,[36][37][38][39]. However, TCD seems to be influenced by deformities of the chest (especially affecting the transverse chest diameter) to a lesser extent than CTR.…”
Section: Discussionmentioning
confidence: 99%
“…Any disagreements with findings between the two readers were evaluated by a third reader with 15 years of experience as a JRS board-certified pulmonologist. Cardiomegaly was defined as a cardiothoracic (CTR) ratio > 0.50, based on posterior-anterior (PA) chest radiographs or a CTR ratio > 0.55 in anterior-posterior (AP) chest radiographs [17]. The abnormalities in chest CT were characterized by consolidation, ground-glass opacity (GGO), centrilobular nodules, interstitial septal thickening, and bronchial wall thickening.…”
Section: Evaluation Of the Chest Radiograph And Ctmentioning
confidence: 99%